Psychosocial groupwork for older adults having substance use and mental health issues - White-Campbell, Marilyn; Luketic, Lea; MacDonald, Stephanie (Groupwork, 2014)
Community Outreach Programs in Addictions (COPA) is a Canadian organization that assists older adults who live with substance misuse and mental health issues. COPA College, a psycho educational mutual aide support group consists of weekly group sessions. The program uses a Solution Focussed approach (De Jong, Insoo Kimberg, 2008) which provides support to socially disadvantaged older adults with substance and mental health issues through a group format. This article sets out to evaluate participant reactions and determine if participants decrease substance use following completion of the group. One-on-one semi-structured interviews with ten participants were conducted. Participants were asked to rate the importance of different aspects of the program and discuss alcohol intake following involvement in the group. Aspects of the program rated highly by all the participants included learning new information, the breadth of topics discussed and the harm reduction approach taken by the program. Finally, the general atmosphere of the group was considered very important, especially being comfortable in the group and combining humour with learning, and an opportunity for reflective, sharing peer support.